Distribution of rare earth elements in surface sediments of the western Sunda Shelf: Constraints from sedimentology and mineralogy. (13th December 2020) - Wu, Kaikai; Liu, Shengfa; Shi, Xuefa; Lou, Zhanghua; Kandasamy, Selvaraj; Wu, Bin; Wang, Kunshan; Cao, Peng; Zhang, Hui; Mohamed, Che Abd Rahim
Abstract: To understand the modern sedimentation and land-sea interaction processes in the Sunda Shelf, we evaluated the rare earth element (REE) compositions, the total organic carbon (TOC) contents, grain sizes, and detrital minerals of 39 surface sediments, collected from the western Sunda Shelf. All of the sampled sediments are characterised by a higher content of light REEs (LREEs) relative to the content of heavy REEs (HREEs) with negative Eu anomalies. The total content of REE (ΣREE) in the sediments ranges from 7 μg/g to 193 μg/g, with an average of 119 μg/g. Due to the uneven spatial distribution of REEs in the study area, a Q-cluster analysis is applied to the mean grain size (Mz), ∑REE, δEu, δCe, (La/Yb)N, and (Gd/Yb)N data. On this basis, the study area can be classified into three geochemical provinces. The north to central zone in the study area is designated as province I, which has the highest REE content among the three provinces. This is a result of the finer grain size, dominance of siderite, and higher TOC contents of the sediments in province I. The REE content of province II in the southwest coastal zone is lower than that of province I due primarily to a coarser grain size and high quartz, biodetritus, and plagioclase contents. Covering the central coastal zone, province III has the lowest REE content among the three provinces because of the extremely coarse grain size and very high quartz and biodetritus contents. The upper continental crust (UCC)-normalised REE patterns differ markedly among the three provinces, thereby indicating different provenances and transport mechanisms. Based on the provenance discrimination plot and the UCC-normalised REE patterns of these three provinces and adjacent rivers, we infer that province I is largely fed by the Mekong and Kelantan rivers. The fine-grained sediments from these rivers are transported to north and central zone by the northeast monsoon current. The Pahang River is identified as the main sediment source of province II. The coarse-grained sediments from this river mostly accumulate near the estuary via hydrodynamic sorting, while finer-grained sediments are transported to the south by the southward coastal currents. The sediments in province III are inferred as being primarily the result of coastal erosion due to the strong wave energy in this area, as well as offshore and longshore sediment transport acting, in parallel to the coast line. Our study can serve as a reference for studying the diffusion and transport processes of mountainous river sediment and the evolution of the paleoclimate and paleoenvironment in tropical low-latitude regions. Highlights: Surface sediments of the western Sunda Shelf can be classified into three geochemical provinces. Grain size and heavy minerals play important constraint roles on REE distribution. Different geochemical provinces have their unique provenances. Erosion, transport and deposition are mainly controlled by northeast monsoon current, coastal current and wave energy.